Effects of Dietary Glycerol Monolaurate on Growth, Antioxidant Capacity and Lipid Metabolism in Cage-Farmed Pompano (Trachinotus ovatus) Juveniles - Lin, Huaxing; Tan, Beiping; Yang, Qihui; Chi, Shuyan; Wei, Hongjie; Wu, Yuancai; Ray, Gyan Watson; Yohana, Mpwaga Alatwinusa (Frontiers in Marine Science, 2022)
Glycerol monolaurate (GML), a representative fatty acid glyceride, was used to promote growth. This study investigated the effects of GML in diets on growth, serum biochemical parameters, antioxidant capacity, liver morphology and lipid metabolism for juvenile pompano Trachinotus ovatus. Six groups of T. ovatus (mean weight = 14.00 ± 0.70 g) were fed with six diets, containing varying GML levels of 0.00% (G0), 0.05% (G5), 0.10% (G10), 0.15% (G15), 0.20% (G20), and 0.25% (G25) for 8 weeks. Fish were reared for in floating cages (length: 1 m; width: 1 m; and height: 2 m). The highest weight gain rate (WGR), specific growth rate (SGR), and protein deposit rate (PDR) were observed in the G15 group (P < 0.05). Hepatic glutathione peroxidase, total antioxidant capacity and superoxide dismutase activities were significantly increased in the G10 and G15 groups compared with the G0 group (P < 0.05), whereas hepatic malondialdehyde (MDA) was significantly reduced in the G10 and G15 groups (P < 0.05). The alkaline phosphatase activity was significantly higher in the G5, G10, G15, and G20 groups than in the G0 group (P < 0.05), and the highest AKP activity was observed in the G15 group. Alanine aminotransferase (ALT) activity was significantly lower in the G10, G15, G20, and G25 groups than in the G0 group (P < 0.05). The addition of GML to the feed significantly reduced triglyceride (TG) content (P < 0.05). In comparison with the G0 group, the G15, G20, and G25 groups had significantly lower total cholesterol content and significantly higher high-density lipoprotein content (P < 0.05). Low-density lipoprotein content was significantly lower in the G5 and G10 groups than in the G0 group (P < 0.05). Serious vacuolation occurred in the G0 group, but the cell boundaries in all added groups were obvious, and the rate of intracellular vacuolization decreased. As the GML level increased, carnitine palmitoyl-transferase Ι mRNA level was significantly up-regulated (P < 0.05). The expression of fatty acid synthesis in the G10, G15, G20, and G25 groups was significantly lower than that in the G0 group (P < 0.05). The expression of sterol regulatory element-binding protein-Ι was significantly lower in the G10, G15, G20, and G25 groups than in the G0 group (P < 0.05). Based on the broken-line model of WGR and PDR corresponding to GML levels, the optimum addition level of dietary GML was 0.14%-0.16% for juvenile T. ovatus. In conclusion, 0.15% GML significantly improved the growth performance, hepatic antioxidant ability, and lipid metabolism and protected the liver for juvenile pompano T. ovatus.